2009
DOI: 10.1007/s10726-009-9155-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Cognitive-Emotional Fugue in Electronic Negotiations

Abstract: A substantial body of literature in CMC and eNS research suggests that communication via textual electronic media is devoid of emotional content as many non-and para-verbal indicators expressing emotions are missing. In order to support these theoretical positions, up to date, studies have mainly focused on the direct expression of emotions. To complement this research, we analyze transcripts from electronic negotiation experiments conducted at three universities in December 2006. By using an exploratory resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 86 publications
0
30
0
Order By: Relevance
“…For instance, Bahl and Milne (2006) used MDS to analyze consumption experiences in narratives, and Griessmair and Koeszegi (2009) employed it to investigate single utterances as well as entire messages of electronic negotiations transcripts with regard to their emotional connotation. Just as with content analysis, MDS is also applicable to in-depth interviews, focus groups, or documents.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Bahl and Milne (2006) used MDS to analyze consumption experiences in narratives, and Griessmair and Koeszegi (2009) employed it to investigate single utterances as well as entire messages of electronic negotiations transcripts with regard to their emotional connotation. Just as with content analysis, MDS is also applicable to in-depth interviews, focus groups, or documents.…”
Section: Discussionmentioning
confidence: 99%
“…A method that allows for the incorporation of an inductive, qualitative component while at the same time producing quantitative data for theory testing is multidimensional scaling (MDS). It has already been extensively used to investigate the underlying dimensions of messages, statements, or expressions in both negotiation (e.g., Griessmair and Koeszegi 2009;Pinkley et al 2005) and emotion research (e.g., Feldman 1995;White 2000). Additionally to the general advantages of MDS (Pinkley et al 2005), this procedure allows for capturing the emotional layer of the exchanged messages (Griessmair and Koeszegi 2009) rather than focusing on explicit emotional language or specific expressions.…”
Section: Emotional Content Of Messagesmentioning
confidence: 99%
“…It has already been extensively used to investigate the underlying dimensions of messages, statements, or expressions in both negotiation (e.g., Griessmair and Koeszegi 2009;Pinkley et al 2005) and emotion research (e.g., Feldman 1995;White 2000). Additionally to the general advantages of MDS (Pinkley et al 2005), this procedure allows for capturing the emotional layer of the exchanged messages (Griessmair and Koeszegi 2009) rather than focusing on explicit emotional language or specific expressions. For alternative, discourse analytic methods to analyze the emotional layer of communication in negotiation, see Martinovsky (2015a) and Martinovsky and Mao (2009).…”
Section: Emotional Content Of Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Guilt proneness was associated with a negative judgment of both making false promises and lying, but unexpectedly, empathy was not related to disapproval of false promises, which are, in fact, not factual lies until some future point when the promise proves to be empty. Complementing spoken language and its emotion-laden messages is research undertaken by Griessmair and Koeszegi ( 2009 ) on negotiation exchanges via email. Using complex content and scaling analyses, these authors found that "factual" statements do indeed convey considerable emotional intent and connotational richness.…”
Section: Social Exchange Theory Emotional Competence and Cooperativmentioning
confidence: 99%